Intentional BlackLove: Space Making, Visionary Solidarity, and Black Feminisms Movement Building. Issue 1 (September 2017) - Nixon, Angelique
Abstract This article shares the highlights and successes of the Black Feminisms Forum and explains the necessity of Black space, Black women's spaces and Black queer space (even within multi-ethnic and women of colour spaces), as well as visionary solidarity that was co-created and intentionally focused onBlackLove . It also discusses the Black Feminisms Forum as a continuous movement-building process for Black feminists activists, artists, community workers and agitators.